Composition and electronic structure of $${\rm SiO}_{\rm x}$$ SiO x / $${\rm TiO}_{\rm y}$$ TiO y /Al passivating carrier selective contacts on n-type silicon solar cells - Christoph Flathmann; Tobias Meyer; Valeriya Titova; Jan Schmidt; Michael Seibt (Scientific Reports, 2023)
Abstract Carrier-selective and passivating SiO $$_{\rm x}$$ x /TiO $$_{\rm y}$$ y heterocontacts are an attractive alternative to conventional contacts due to their high efficiency potentials combined with relatively simple processing schemes. It is widely accepted that post deposition annealing is necessary to obtain high photovoltaic efficiencies, especially for full area aluminum metallized contacts. Despite some previous high-level electron microscopy studies, the picture of atomic-scale processes underlying this improvement seems to be incomplete. In this work, we apply nanoscale electron microscopy techniques to macroscopically well-characterized solar cells with SiO $$_{\rm x}$$ x /TiO $$_{\rm y}$$ y /Al rear contacts on n-type silicon. Macroscopically, annealed solar cells show a tremendous decrease of series resistance and improved interface passivation. Analyzing the microscopic composition and electronic structure of the contacts, we find that partial intermixing of the SiO $$_{\rm x}$$ x and TiO $$_{\rm y}$$ y layers occurs due to annealing, leading to an apparent thickness reduction of the passivating SiO $$_{\rm x}$$ x . However, the electronic structure of the layers remains clearly distinct. Hence, we conclude that the key to obtain highly efficient SiO $$_{\rm x}$$ x /TiO $$_{\rm y}$$ y /Al contacts is to tailor the processing such that the excellent chemical interface passivation of a SiO $$_{\rm x}$$ x layer is achieved for a layer thin enough to allow efficient tunneling through the layer. Furthermore, we discuss the impact of aluminum metallization on the above mentioned processes.